Influence of the common mode impedance paths on the design of the EMI filters used with SiC-buck converter - Kotny, J.-L.; Duquesne, T.; Idir, N. (Advanced Electromagnetics, 2015)
This paper deals the design of EMI filter associated with buck converter using fast semiconductors silicon carbide SiC (diode and transistor JFET). To comply with EMC standards, a filter design method based on an equivalent electrical circuit is proposed. The aim is to identify the different values of the EMI filter elements but also to obtain the limits values of the parasitic elements of the passive components which have a major influence on the attenuation of the filters. The purpose is to study the influence of the modification of the common mode propagation paths before and after the installation of the filter. A solution is also proposed to reduce the conducted disturbances that occur at high frequency caused by the fast SiC components.The comparison of the simulation results with the measurements data carried out on a DC-DC converter without and with the EMI filter, shows the effectiveness of the proposed design approach.